The Papajar Tradition as a Cultural Communication Practice in Fostering Social Cohesion among the Community of Cianjur Regency - Erlan Gantira (P3M STAI Kuningan, 2026)
The Papajar tradition is a Sundanese local tradition practiced in Cianjur Regency before Ramadan as an expression of gratitude, togetherness, and socio-spiritual preparation. Amid modernization and the increasing shift toward digital communication, maintaining face-to-face cultural interaction and intergenerational transmission has become increasingly important. This study aims to analyze the Papajar tradition as a cultural communication practice and examine its contribution to fostering social cohesion within the community of Cianjur Regency. This study employed a qualitative approach with a descriptive design. Data were collected through participant observation, in-depth interviews, documentation, and literature review involving community leaders, traditional and religious leaders, village officials, and local residents who actively participate in Papajar activities. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, supported by cultural communication, interpersonal communication, ritual communication, and social capital perspectives. The findings show that Papajar transmits cultural values through the Sundanese language, silaturahim, botram, respect for elders, and collective participation. These practices strengthen interpersonal relationships, reinforce cultural identity, and develop bonding and bridging social capital through trust, solidarity, participation, and social integration. The findings imply that preserving Papajar is important not only for safeguarding local cultural heritage but also for sustaining culturally meaningful communication spaces and strengthening social cohesion amid contemporary social transformation.